2014
DOI: 10.1186/1471-2474-15-438
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 4 alters cartilage homeostasis in human osteoarthritis

Abstract: BackgroundOsteoarthritis (OA) is the most common degenerative joint disorder, and a major cause of pain and disability among the elderly. Histone deacetylase 4 (HDAC4) has been shown to be a key regulator of chondrocyte hypertrophy during skeletogenesis. The aims of present study were to investigate the expression of HDAC4 in normal and OA cartilage and its potential roles during OA pathogenesis.MethodsThe knee cartilage specimen (a total of 18, 12 female and 6 male) were obtained from primary OA patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…27 The expression of HDAC4 was increased in OA chondrocytes, whereas knockdown of HDAC4 attenuated the induction of catabolic gene expression in chondrocytes. 28 In another study, direct correlation was observed in the enhanced expression of MMP-13 and increased HDAC7 levels in OA cartilage. 29 Treatment with TSA, valproic acid, or MS-275 blocks the cytokine-induced expression of MMP-1 and -13 in human articular chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…27 The expression of HDAC4 was increased in OA chondrocytes, whereas knockdown of HDAC4 attenuated the induction of catabolic gene expression in chondrocytes. 28 In another study, direct correlation was observed in the enhanced expression of MMP-13 and increased HDAC7 levels in OA cartilage. 29 Treatment with TSA, valproic acid, or MS-275 blocks the cytokine-induced expression of MMP-1 and -13 in human articular chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In Wnt-5a mRNA silencing, the passage 2 chondrocytes were stimulated for 6 h with IL-1β as previously described (25). The OA-like chondrocytes were divided into three groups: Group I, incubated with complete DMEM for 7 days; group II, incubated with complete DMEM supplemented with empty lentiviral vector for 7 days; group III, incubated with complete DMEM supplemented with LV-Wnt5a-RNAi for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…The abnormal expression of HDAC4 in osteoarthritic cartilage suggests its involvement in promoting the catabolic activity of chondrocytes associated with OA pathogenesis. 6 A significant elevation of HDAC7 in the cartilage of OA patients is reported to contribute to cartilage degradation via promoting MMP-13. 7 These studies suggest that inhibiting certain HDACs may be useful in the management of OA.…”
Section: Role Of Hdacs In Oa Pathogenesismentioning
confidence: 99%